Efecto del Asoleado y Almacenamiento en el Rendimiento de Tuberculo – Semilla de papa (Solanum tuberosum L), Infestada con punta morada (Candidatus liberibacter), Variedad Iniap Libertad en Ceyspa – UTC, Provincia de Cotopaxi, 2022. - Llano Espinosa, Alison Nicole (2022)
The research was carried out at the Technical University of Cotopaxi in the campus Salache Parish Eloy Alfaro, Canton Latacunga, Province of Cotopaxi, the site is at an altitude of 2757,591 whose geographical coordinates are: 78 ° 37 '19,16 "North latitude and 78 ° 37' 72" East latitude. Presenting an average annual temperature of 12 to 22 ° C and an annual rainfall of 220 mm, with heliophany of 12 hours, also presenting annual clouds of 4.7/8 also has winds that go from the southeast and northeast. The general objective raised was to form information on the effect of sunning and storage technologies on the yield of potato tuber- seed Iniap Libertad, the following specific objectives were proposed: analyze which of the seed categories had a dehydration in the sunny and storage state, evaluate the behavior of the shoots in the storage and sunny for the obtaining of potato seed, determine the best storage system of potato in tarp rala, normal tarp, plastic drawers and weathering. For this investigation, the harvest and classification of the tubers by first, second and third categories were carried out, then the potatoes were placed in different forms of storage such as: sunny, normal canvas, plastic drawers and thin canvas, once all this process was done. Data collection was carried out each week such as length, width, weight of the tuber and growth of sprouts, for which twenty potato seeds infested with purple tip (Candidatus Liberibacter) were selected. For this investigation, a statistical analysis was carried out using average tables. and graphs including a 5% tukey test for categories and types of storage with the data obtained, the behavior of the tubers was determined - seed in sunny storage where the normal canvas was obtained as the best storage since it had the appearance of shoots in its majority and a better dehydration was the tubers exposed to the elements and also did not present development of l you buds.